An overview of knowledge management research viewed through the web of science (1993-2012) - Qiu, Junping; Lv, Hong (Aslib journal of information management, 2014)
Purpose – The purpose of this paper is to present a bibliometric analysis of scientific output of the knowledge management (KM), the aim being to offer an overview of research activity in this field and characterize its most significant aspects. In addition, this study aims to quantitatively analyze KM research trends, forecasts, and citations from 1993 to 2012 in Web of Science (WOS). Design/methodology/approach – A total of 12,925 documents related to KM research were collected from following databases: Science Citation Index Expanded, Social Sciences Citation Index, Arts & Humanities Citation Index, Conference Proceedings Citation Index-Science, and Conference Proceedings Citation Index-Social Science & Humanities. These documents were carefully reviewed and subjected to bibliometric data analysis techniques. Findings – A number of research questions pertaining to patterns in scientific outputs, subject categories and major journals, author keywords frequencies, characteristics of the international collaboration, most cited papers and significant papers distribution of KM research were proposed and answered. In addition, there are five research sights on KM research are as follows: management science, computer science, information science, business, and engineering. Based on these findings, many implications emerged that improve one's understanding of the identity of KM as a distinct multi-discipline scientific field. Research limitations/implications – Comprehensiveness and inclusiveness of the analyzed KM-related data set in WOS because of some KM-centric journals are not indexed by Thomson Reuters. Originality/value – The paper offers an overview and evaluation of research activity into the KM viewed through the WOS during 1993-2012.